Security Analysis of an IoT Architecture for Healthcare - Teresa Villalba, M.; de Buenaga, Manuel; Gachet, Diego; Aparicio, Fernando (Internet of Things. IoT Infrastructures, 2016)
Security issues of IoT devices are increasing with their massive use in healthcare. Recollection of data from devices is not clear to the users so far, and different problems arise including confidentiality, integrity and availability of the information. We analyze security issues mainly related to IoT data storage and transmission in our proposal of healthcare system architecture including cloud services and big data processing of information. We identify protocols needed and security problems including authentication, transmission of data to the cloud, as well as their insufficient anonymization process and the opaque procedure for users in order to control the storage of their data.